New data on the taxonomy, ecology, and conservation of the rediscovered Louisea edeaensis (Bott, 1969) (Brachyura: Potamoidea: Potamonautidae), an endangered freshwater crab from Cameroon - Ndongo, Pierre A. Mvogo; Rintelen, Thomas Von; Schubart, Christoph D.; Albrecht, Christian; Tamesse, Joseph L.; Cumberlidge, Neil (Zootaxa, 2017)
The rare and endangered Cameroonian potamonautid freshwater crab Louisea edeaensis (Bott, 1969) was recently rediscovered during a biological inventory of the freshwater decapods of southern Cameroon. The previous record dated back more than 100 years. The new specimens allow an updated diagnosis of the species based on comparisons of important taxonomic characters. Photographs of the carapace, gonopods, third maxillipeds, and chelipeds of the largest adult male specimen from Lake Ossa, Cameroon are provided, as are the first photographs of living specimens. The conservation implications of the new data on habitat, population structure, distribution, and threats for this rare and endangered species are discussed.